(untitled) (Transport systems and technologies, 2019)
In the article the questions of definition of rational inter-repair runs and application of the automated system of computer simulation of network norms are considered. This makes it possible to make full use of the resource of the components and parts of the locomotive, as well as to reduce the rises for maintenance and repair. The untimely setting of locomotive results in a deterioration of its technical condition and an increase in the cost of repair and preventive maintenance. The division of the territory of Ukraine according to the climatic conditions of operation of rolling stock and the rigidity of the service condition of the service should be proposed in order to increase the reliability of trouble-free operation. The approach to establishing the optimal structure of maintenance and repair system based on statistical data and analysis of the reliability of locomotive nodes is formulated. The basic parameters of the rational system of maintenance and repair for the specific operating conditions have been found, the numerical values of the correction factors confirmed by experimental operation of the locomotives of the ChME 3 (P) series on the Ukrzaliznytsia network have been theoretically determined, which allow the rational use of economic resources.